Incidence and Risk Factors of Early-onset Glaucoma following Pediatric Cataract Surgery in Egyptian Children: One-year Study - I Gawdat, Ghada (J Curr Glaucoma Pract, 2017)
AIM: To study the incidence and risk factors of glaucoma occurring within 1 year following pediatric cataract surgery in Egyptian children. MATERIALS AND METHODS: This is a prospective nonrandomized study conducted at Aburich Children’s Hospital, over a period of 1 year on a cohort of Egyptian patients with congenital and infantile cataract. One hundred and fifty eyes of 88 patients were enrolled in this study. All the patients underwent anterior approach removal of lens matter, whereas primary intraocular lens (IOL) implantation was carried at the age of 1 and 2 years for unilateral and bilateral cases respectively. Intraocular pressure (IOP) was measured at 1 week, 1 month, 3 months, 6 months, 9 months, and 1 year. For those who developed glaucoma, time of diagnosis and associated risk factors were reported. RESULTS: The incidence of glaucoma was 11.33% (17 of 150 eyes), while incidence of glaucoma suspect was 0.67% (1 of 150 eyes) in the first year following cataract surgery. The majority of the cases (66.7%) were discovered in the first 3 months postcataract surgery. Age at time of cataract surgery, the state of aphakia/pseudophakia, persistent fetal vasculature (PFV), and microphthalmia were not found to be significant predictors of early-onset glaucoma in our study. CONCLUSION: Aphakic glaucoma continues to be a devastating condition with high incidence during first year following cataract surgery. CLINICAL SIGNIFICANCE: Regular follow-up should start as early as possible following cataract surgery. Further prospective studies with larger study population are required. How to cite this article: Gawdat GI, Youssef MM, Bahgat NM, Elfayoumi DM, Eddin MAS. Incidence and Risk Factors of Early-onset Glaucoma following Pediatric Cataract Surgery in Egyptian Children: One-year Study. J Curr Glaucoma Pract 2017;11(3):80-85.